Clinical and esthetic outcomes of two different prosthetic workflows for implant‐supported all‐ceramic single crowns—3 year results of a randomized multicenter clinical trail. Issue 5 (25th February 2020) - Wittneben, Julia‐Gabriela; Gavric, Jelena; Sailer, Irena; Buser, Daniel; Wismeijer, Daniel
Abstract: Objective: The aim of this randomized multicenter clinical trial was to evaluate and compare the performance of anterior all‐ceramic implant crowns based either on prefabricated zirconia abutments veneered with pressed ceramics or on CAD/CAM zirconia abutments veneered with the hand build‐up technique. The null hypothesis was that there is no statistically significant difference between the two study groups. Material and methods: Forty implants were inserted in sites 14–24 (World Dental Federation [FDI]) in two centers, the Universities of Bern and Geneva, Switzerland. Twenty patients each were randomized into either Group A and restored with one‐piece single crown made of a prefabricated zirconia abutment with pressed ceramic, or Group B using an individualized CAD/CAM zirconia abutment with the hand‐layered technique. After 3 years, clinical, esthetic, and radiographic parameters were assessed. Results: Group A exhibited one dropout patient and one failure resulting in a survival rate of 89% after 3 years and two failures for Group B (90%). Clinical parameters presented healthy peri‐implant soft tissues. Overall, no crestal bone level changes were observed (mean DIB of 0.13 mm [Group A] and 0.24 mm [Group B]). There were no significant differences at baseline, 6 months, and 1 and 3 years for DIB values between the two groups. PES and WES values evaluated at all three time points indicated stability over time for both groups and pleasing esthetic outcomes. Conclusions: Both implant‐supported prosthetic pathways represent a valuable treatment option for the restoration of implant crowns in the anterior maxilla.